Exposure of Infants to Gradient Fields in a Baby MRI Scanner. Issue 2 (10th January 2022) - Tang, Fangfang; Giaccone, Luca; Hao, Jiahao; Freschi, Fabio; Wu, Tongning; Crozier, Stuart; Liu, Feng
Abstract : In pediatric magnetic resonance imaging (MRI), infants are exposed to rapid, time‐varying gradient magnetic fields, leading to electric fields induced in the body of infants and potential safety risks (e.g. peripheral nerve stimulation). In this numerical study, the in situ electric fields in infants induced by small‐sized gradient coils for a 1.5 T MRI scanner were evaluated. The gradient coil set was specially designed for the efficient imaging of infants within a small‐bore (baby) scanner. The magnetic flux density and induced electric fields by the small x, y, z gradient coils in an infant model (8‐week‐old with a mass of 4.3 kg) were computed using the scalar potential finite differences method. The gradient coils were driven by a 1 kHz sinusoidal waveform and also a trapezoidal waveform with a 250 µs rise time. The model was placed at different scan positions, including the head area (position I), chest area (position II), and body center (position III). It was found that the induced electric fields in most tissues exceeded the basic restrictions of the ICNIRP 2010 guidelines for both waveforms. The electric fields were similar in the region of interest for all coil types and model positions but different outside the imaging region. The y ‐coil induced larger electric fields compared with the x ‐ and z ‐ coils. Bioelectromagnetics. 43:69–80, 2022. © 2021 Bioelectromagnetics Society.